The influence of sand and gravels on root growth of maize seedlings - Vine, P.N.; Lal, R.; Payne, D. (Ovid Technologies, 1981)
We prepared sand and gravelly sand media in rigid cylinders, with different proportions and sizes of gravels and sands at various water tensions. Cores of forest topsoil were used for comparison. We measured the growth of pregerminated maize seedlings 72 hours after transplanting them into these media. Compared with growth in forest topsoil, root lengths averaged over sand and gravelly sand media were 27 percent less, depth of penetration was 65 percent less, and primary seminal root diameter was 36 percent greater. Further, primary seminal roots were significantly shorter and shallower, and penetrometer resistance was greater with the higher proportions of gravel, the smaller sizes of gravel and sand, and the lower soil water tension. Penetration resistance increased nearly sixfold as the volumetric percentage of gravel increased from 0 to 45, with a corresponding reduction in depth of root penetration below the seed of 30 percent. The resistance of close-packed sands to root penetration and the further hardening effect of gravel highlight the importance of promoting root-size pores to bypass mechanical resistance.